UPAYA PEMERINTAH DAERAH KABUPATEN TEGAL DALAM RANGKA MELINDUNGI KESENIAN TARI TOPENG KHAS KABUPATEN TEGAL - Ananda Putri Sekar Pratama, Etty Susilowati, Paramita Prananingtyas (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2012)
Regional Government of Tegal is one of the Indonesian regions that has various culture, such as art of Topeng Dance. It is a must preserved region’s legacy to prevent extinction or claiming. The country and regional government of Tegal have an obligation protecting regional culture variety as written in article 10 (2) and article 12 (1) The Indonesian Copyright Act No. 19 Year 2002 and also statute No. 32 Year 2004 about Regional Government gives the regional government of Tegal the right to manage and protect its legacy.